Study of experimental-industrial design of rotary vortex machine - Питак, Инна Вячеславовна (Technology audit and production reserves, 2014)
Comparative assessment of machines by the amount of energy consumed is presented in the paper. For comparison, machines for air purification from dust with the particle size of 3-5 microns were selected. All considered scrubbing machines achieve maximum purification efficiency, but with a different amount of energy spent. A machine with guiding elements reaches maximum purification efficiency with energy consumption by 40% less than a machine with a smooth setting. Testing of industrial design was carried out during purification of gas emissions from cement production ingredients, and purification of flue gases of boiler houses. In both cases using machines not only provided a reduction in dust emissions, but also harmful gas impurities. Dust-gas-air mixture, which has been purified in the rotary vortex machine meets the requirements of state sanitary rules and norms, and may be released into the atmosphere. Testing of the machine has shown that rotary vortex machine with guiding elements, installed on the torus surface provides the purification efficiency of up to 98%, which indicates the usefulness of guiding elements in the rotary vortex machine design. Experiments have shown the appropriateness of using the machine in the technological scheme of gas purification since it provides an effective capture of fine particles.